Effects of Dendrobium Officinale Polysaccharides on Brain Inflammation of Epileptic Rats - Lin Zhang; Hua Peng; Jin Xu; Yixin Xu; You Yin; Bin He; Jianhua Zhuang (International Journal of Polymer Science)
Objective. To investigate the effects of Dendrobium officinale polysaccharides (DOPS) on the expression of inflammatory factors IL-1β and TNF-α and the MKP-1/MAPK signal pathway. Methods. PTZ-induced epileptic rat models were established. The rats were randomly divided into four groups: the control group, the DOPS group, the model group, and the DOPS intervention group. RT-PCR was used to measure the mRNA expression of IL-1β and TNF-α in the hippocampi of all groups; western blot was used to measure the protein expression of IL-1β and TNF-α and phosphorylation of ERK1/2, JNK, p38, and MKP-1 in the hippocampi of all groups at weeks 1, 2, 3, and 4 after modeling. Results. At weeks 1, 2, 3, and 4 after modeling, there were no significant differences between the control group and the DOPS group in the mRNA and protein expression of IL-1β and TNF-α and phosphorylation of ERK1/2, JNK, p38, and MKP-1 (all P>0.05); the mRNA and protein expression of IL-1β and TNF-α and phosphorylation of ERK1/2, JNK, and p38 were significantly increased, while the phosphorylation of MKP-1 was decreased in the model group compared with the control group. The mRNA and protein expression of IL-1β and TNF-α and phosphorylation of ERK1/2, JNK, and p38 were significantly decreased, while the phosphorylation of MKP-1 was increased in the DOPS intervention group compared with the model group. Conclusion. DOPS can reduce PTZ-induced brain inflammation and seizures of epileptic rats by inhibiting IL-1β, TNF-α, and MAPK signal pathways.